2014
DOI: 10.1111/bju.12818
|View full text |Cite
|
Sign up to set email alerts
|

Health‐related quality of life from a prospective randomised clinical trial of robot‐assisted laparoscopic vs open radical cystectomy

Abstract: Objective To compare health‐related quality‐of‐life (HRQoL) outcomes for robot‐assisted laparoscopic radical cystectomy (RARC) with those of traditional open radical cystectomy (ORC) in a prospective randomised fashion. Patients and Methods This was a prospective randomised clinical trial evaluating the HRQoL for ORC vs RARC in consecutive patients from July 2009 to June 2011. We administered the Functional Assessment of Cancer Therapy–Vanderbilt Cystectomy Index questionnaire, validated to assess HRQoL, preop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
47
1
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(59 citation statements)
references
References 28 publications
(48 reference statements)
2
47
1
6
Order By: Relevance
“…A recent prospective, randomized trial was conducted to evaluate HRQoL outcomes in patients who underwent ORC or RARC, and used the validated Functional Assessment of Cancer Therapy-Vanderbilt Cystectomy Index (FACT-VCI). 24 In their analysis, they found no significant differences in the HRQoL outcomes: specifically, physical well-being, social and/or family, and emotional well-being. In addition, changes in the FACT-VCI were similar across both cohorts at the 3-, 6-, 9-, and 12-month intervals, with a HRQoL return to baseline at 3 months after RC.…”
Section: Quality Of Lifementioning
confidence: 90%
See 1 more Smart Citation
“…A recent prospective, randomized trial was conducted to evaluate HRQoL outcomes in patients who underwent ORC or RARC, and used the validated Functional Assessment of Cancer Therapy-Vanderbilt Cystectomy Index (FACT-VCI). 24 In their analysis, they found no significant differences in the HRQoL outcomes: specifically, physical well-being, social and/or family, and emotional well-being. In addition, changes in the FACT-VCI were similar across both cohorts at the 3-, 6-, 9-, and 12-month intervals, with a HRQoL return to baseline at 3 months after RC.…”
Section: Quality Of Lifementioning
confidence: 90%
“…48,52,58 Quality of life studies that compared type of diversion outcomes 59 have been conducted, as have studies that compared approach, 60 but very limited data exist on comparison of types of diversion (continent vs. incontinent) and the approach (ICUD vs. ECUD). 24 Results for ICNB continence are promising. At 12 months, Tyritzis et al reported 88.2% and 88.9% daytime continence and 73.5% and 81.2% nighttime continence in male patients with nerve-sparing and nonnerve-sparing neobladder, respectively.…”
Section: Controversies Regarding Approach and Diversionmentioning
confidence: 98%
“…An area of developing interest has been in robot-assisted and laparoscopic cystectomy although, to date, no study has yet focussed on comparing QoL outcomes between neobladder and other diversion types in these population groups. 22,[29][30] Conclusions Neobladder has indeed stood the test of time with recent studies predominantly concluding that such a diversion is associated with superior QoL scores than other diversion types. With the advent of minimally invasive techniques and better quality studies it remains to be seen whether these recent trends with neobladder reconstruction can be sustained.…”
Section: Page 5 Of 16mentioning
confidence: 99%
“…Messer ve ark. yaptığı prospektif randomize çalışmada ise robotik ve açık cerrahi karşılatılırmıştır (60). Yirmişer kişilik iki gruba ayrılan hastalara Therapy-Vanderbilt Cystectomy Index sorgulaması ve HRQoL uygulanmıştır.…”
Section: Robotik Sistektomi Ve üRiner Diversiyonda Yaşam Kalitesiunclassified